Effect of Hydrogen Peroxide Sterilization on Fertility, Embryo Viability, Hatchability, and Hatch Weight of Purebred Chicken Eggs Laying Eggs Crossed With Bangkok Chickens (Pascasarjana Universitas Sulawesi Tenggara, 2022)
This research aimed to evaluate the effect of hydrogen peroxide sterilization on fertility, embryo viability, hatchability and hatching weight of laying hens’ egg that are crossbreed with fighting cock. This reseach used Completely Randomized Design (CRD) as the design of research with 3 treatments and 6 replications, so there were 18 experimental units. Each experimental unit consist of 10 eggs so that the number of hatching eggs was used 180 eggs. Treatment consist of: P0 = water without hydrogen peroxide addition, P1 = water contained 2% of hydrogen peroxide, P2 = water contained 4% of hydrogen peroxide. The reseach variables were fertility, embryo viability, hatchability and hatching weight. The result of research showed that the average percentage of fertility, embryo viability, hatchability and hatching weight of chicken eggs in this research were 78,47%, 90,02%, 80,34% and 41,67g respectively. The result of the analysis of variance showed that the treatment had effect on fertility, but had no significant effect on embryo viability, hatchability and hatching weight of laying hens’ egg that are crossbreed with fighting cock. The conclusion of this research was eggs that cleaned with 2% hydrogen peroxide solution produced a high percentage of fertility